Preparation method of lithium manganese iron phosphate battery positive electrode material

In the preparation of the positive electrode material of lithium manganese iron phosphate battery, electrospinning and heat treatment combined with composite carbon nanotubes were used to solve the problems of the material's cyclic performance and structural stability, and high energy density and excellent electrochemical performance were achieved. .

CN119284855APending Publication Date: 2025-01-10GUANGXI JINMAO TITANIUM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411278244.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The circulation performance, rate performance and structural stability of the existing lithium manganese iron phosphate battery positive electrode materials are poor, making it difficult to meet the high requirements for battery performance of new energy vehicles.

Method used

After stirring in N,N-dimethylformamide solvent with lithium, manganese, iron, phosphate roots and polyacrylonitrile, the positive electrode material precursor was obtained by sonication and electrospinning, and then in a tube furnace. Heat treatment was carried out, composite carbon nanotubes were mixed and pressed, and the positive electrode material of lithium manganese iron phosphate battery was prepared.

Benefits of technology

It improves the circulation performance, structural stability and rate performance of the cathode material of lithium manganese iron phosphate battery, extends the service life of the battery, enhances the chemical and physical stability of the material, reduces internal resistance, and improves the energy output capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040871530000031
    Figure BDA0005040871530000031
  • Figure BDA0005040871530000151
    Figure BDA0005040871530000151
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium manganese iron phosphate battery positive electrode material, and belongs to the technical field of battery positive electrode material preparation. The preparation method of the lithium manganese iron phosphate battery positive electrode material comprises the following steps: (1) adding a lithium source, a manganese source, an iron source, a phosphate radical source and polyacrylonitrile into a container, then adding N, N-dimethylformamide as a solvent, stirring under a water bath heating condition to obtain a spinning solution, stirring and mixing the spinning solution with a composite organic matter, and then, carrying out ultrasonic treatment to obtain a precursor solution; carrying out ultrasonic treatment, and then carrying out electrostatic spinning to obtain a positive electrode material precursor; (2) after aging the positive electrode material precursor, transferring the positive electrode material precursor into a tubular furnace for heat treatment to obtain a carbonized positive electrode material; and (3) carrying out ball-milling mixing on the composite carbon nanotube and the carbonized positive electrode material, and pressing to obtain the lithium manganese iron phosphate battery positive electrode material. The positive electrode material prepared by the method has excellent cycle performance, structural stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode material preparation, and specifically relates to a method for preparing a positive electrode material for a lithium manganese iron phosphate battery. Background Art

[0002] With the global emphasis on environmental protection and energy sustainability, the market demand for new energy vehicles, especially electric vehicles, has risen sharply, and higher requirements have been placed on the energy density, safety, cycle life and other performance of power batteries. As a traditional positive electrode material, lithium iron phosphate has the advantages of high safety and low cost, but its energy density is close to the theoretical limit and it is difficult to meet the needs of long-range electric vehicles. In this context, lithium iron phosphate, as an upgraded material of lithium iron phosphate, has gradually become a hot spot in industry research due to its higher energy density, excellent thermal stability and environmental friendliness. Researchers are committed to developing efficient and stable preparation methods for lithium iron phosphate positive electrode materials. By continuously exploring and optimizing the preparation process and modification technology, they hope to prepare high-performance, low-cost lithium iron phosphate positive electrode materials to promote the further development of new energy vehicles and energy storage technologies.

[0003] Patent CN 117401663 A discloses a method for preparing positive electrode materials of lithium iron manganese phosphate batteries with different particle sizes, the steps are as follows: adding a lithium source and a phosphorus source to a mixed solution of water and different organic solvents, and stirring thoroughly to obtain solution a; adding solution a to a reactor for stirring, and nitrogen protection is required during the stirring process; dissolving an iron source and a manganese source in water in proportion to obtain solution b, and dripping solution b into a reactor in a stirring state to obtain a final mixed solution c; turning on the reactor heating system, heating to the target temperature and then keeping warm; after the reaction is completed, collecting the product, filtering, eluting, and drying to obtain positive electrode materials of lithium iron manganese phosphate lithium-ion batteries with different particle sizes. Adding different organic solvents can realize the study of the particle size of lithium iron manganese phosphate, so that it can be better applied to different fields, but the cycle performance, rate performance and structural stability of the positive electrode materials of lithium iron manganese phosphate batteries prepared by this method still have room for improvement. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, so as to solve the technical problems of poor cycle performance, rate performance and structural stability of the positive electrode material for a lithium manganese iron phosphate battery in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, comprising the following steps:

[0007] Step (1): adding a lithium source, a manganese source, an iron source, a phosphate source and polyacrylonitrile into a container, then adding N,N-dimethylformamide as a solvent, stirring under heating conditions in a water bath to obtain a spinning solution, stirring and mixing the spinning solution with the composite organic matter, ultrasonically treating, and then electrospinning to obtain a positive electrode material precursor;

[0008] Step (2): after aging the cathode material precursor, transferring it to a tube furnace for heat treatment to obtain a carbonized cathode material;

[0009] Step (3): After ball-milling the composite carbon nanotubes and the carbonized positive electrode material, the mixture is pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

[0010] Preferably, in step (1), the lithium source is composed of one or more combinations of lithium carbonate, lithium hydroxide, lithium acetate and lithium chloride; the manganese source is composed of one or more combinations of manganese tetraoxide, manganese dioxide, manganese hydroxide and manganese acetate; the iron source is composed of one or more combinations of ferric phosphate, ferrous oxide, ferrous sulfate and ferrous oxalate; and the phosphate source is composed of one or more combinations of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.

[0011] Preferably, in step (1), the molar ratio of the lithium source, manganese source, iron source and phosphate source is (1.5-1.95): (1.2-1.56): (0.3-0.39): (1.5-1.95), the water bath heating temperature is 70-80°C, the stirring time is 6-8h, and the amount ratio of the spinning solution to the composite organic matter is (30-50) mL:

[0012] (5-8) g, the ultrasonic treatment time was 15-20 min, during the electrospinning process, the inner diameter of the stainless steel needle was 0.6 mm, the capacity was 10 mL, the voltage during the electrospinning process was 20 kV, the distance between the needle and the collecting device was 12 cm, the spinning solution flow rate was 0.4 mL / h, the humidity was 25-30%, and the temperature was 24-28 °C.

[0013] Preferably, the method for preparing the composite organic matter comprises the following steps:

[0014] Q1: Add 4,4-dibromomethylbiphenyl and m-tribromomethylbenzene to a container, then add dichloroethane, after ultrasonic treatment, add anhydrous ferric chloride under nitrogen protection, heat and stir, then increase the temperature to continue the reaction, after the reaction is completed, dilute, filter, wash, and dry to obtain the precursor;

[0015] Q2: Add the precursor to a container, add toluene, stir magnetically, then add tetramethylpropylenediamine, react in an oil bath, and after the reaction is completed, dilute, filter, soak, filter, wash, and dry to obtain a composite organic matter.

[0016] In the above process, the synthesis reaction formula of the composite organic matter is as follows:

[0017]

[0018] Preferably, in Q1, the molar ratio of 4,4-dibromomethylbiphenyl, m-tribromomethylbenzene and anhydrous ferric chloride is (1-2): (1.1-2.1): (2-4), the ultrasonic treatment time is 20-30 min, the heating and stirring temperature is 40-50°C, the stirring time is 1-2 h, the heating temperature is 80-85°C, the continued reaction time is 1-2 h, it is diluted with a 50vt% methanol solution, and the drying temperature is 80-90°C; in Q2, the amount ratio of the precursor, toluene and tetramethylpropylenediamine is (0.18-0.36) g: (5-10) mL: (1-2) mL, the oil bath reaction temperature is 90-92°C, the reaction time is 70-74 h, it is soaked in a 50vt% methanol solution for 1-3 days, and the drying temperature is 80-82°C.

[0019] Preferably, in the step (2), the aging time is 10-12 hours, and the heat treatment process is: first pre-oxidation is carried out, the pre-oxidation temperature is 230°C, the heating rate is 2°C / min, and the holding time is 2 hours, and then a carbonization stage heat treatment is carried out, the carbonization stage heating rate is 5°C / min, the carbonization time is 4 hours, the carbonization temperature is 750°C, and the carbonization time is 6 hours.

[0020] Preferably, the method for preparing the composite carbon nanotubes comprises the following steps:

[0021] S1: adding multi-walled carbon nanotubes into a container, adding a mixed solution of concentrated nitric acid and concentrated sulfuric acid, heating and refluxing for reaction, adding distilled water after the reaction is completed, standing, removing the supernatant, filtering, washing, and drying to obtain acidified carbon nanotubes;

[0022] S2: mixing the acidified carbon nanotubes with thionyl chloride, heating under reflux under nitrogen protection, distilling after the reaction is completed to obtain acyl chloride carbon nanotubes, mixing the acyl chloride carbon nanotubes with anhydrous toluene, adding sodium azide, heating under reflux under nitrogen protection, adding tetrahydrofuran solution after the reflux is completed, continuing to heat and reflux, filtering, washing, and vacuum drying after the reflux is completed to obtain modified carbon nanotubes;

[0023] S3: The modified carbon nanotubes and hydrochloric acid are mixed, ultrasonically dispersed, and aniline is added. The mixture is stirred magnetically to obtain a mixed solution. Meanwhile, ammonium persulfate is dissolved in the hydrochloric acid. After mixing evenly, the mixture is added dropwise to the mixed solution. The dropping time is controlled. After the dropping is completed, the reaction is continued. After the reaction is completed, the mixture is filtered, washed, dried, ground, and sieved to obtain composite carbon nanotubes.

[0024] In the above process, the multi-walled carbon nanotubes are first mixed with an acid mixed solution to obtain acidified carbon nanotubes containing carboxyl groups on the surface, which are then reacted with thionyl chloride. Under heating conditions, a substitution reaction occurs to obtain acyl chloride carbon nanotubes, which are then reacted with sodium azide and heated under reflux to obtain modified carbon nanotubes containing amino groups on the surface. The modified carbon nanotubes are mixed with aniline for reaction, and potassium persulfate is used as an initiator and oxidant. The free radicals generated by decomposition will attack the aniline molecules, causing them to polymerize with the modified carbon nanotubes (the amino groups on the surface of the modified carbon nanotubes can serve as active sites for polymerization reactions) to obtain composite carbon nanotubes.

[0025] Preferably, in S1, the amount ratio of multi-walled carbon nanotubes, concentrated sulfuric acid, concentrated nitric acid and distilled water is (2.4-3.6) g: (90-135) mL: (30-45) mL: (50-75) mL, the heating reflux reaction temperature is 80-85°C, the reaction time is 2-3 h, and the drying temperature is 60-65°C; in S2, the amount ratio of acidified carbon nanotubes and thionyl chloride is (2-3) g: (80-100) mL, and the heating reflux temperature is 70-75°C The reflux time is 10-12h, the dosage ratio of acyl chloride carbon nanotubes, anhydrous toluene, sodium azide and tetrahydrofuran solution is (1.5-2.3)g:(50-75)mL:(10-15)mg:(50-75)mL, the heating reflux temperature is 60-70℃, the time is 6-8h, the volume fraction of tetrahydrofuran solution is 50vt%, the heating reflux temperature is 80-85℃, the time is 1-2h, and the vacuum drying temperature is 80-85℃, and the time is 20-24h.

[0026] Preferably, in S3, the dosage ratio of modified carbon nanotubes, hydrochloric acid and aniline is (0.38-0.76) g: (150-300) mL: (1.5-3) mL, the ultrasonic dispersion time is 30-45 min, the dosage ratio of ammonium persulfate, hydrochloric acid and mixed solution is (3.75-7.5) g: (75-150) mL: (150-300) mL, the dropwise addition time is 4-6 h, the continued reaction time is 10-12 h, and the mixture is first washed with acetone 3-5 times, and then washed with distilled water until the filtrate is clear.

[0027] Preferably, in step (3), the ratio of the composite carbon nanotubes to the carbonized positive electrode material is (1-3) g: (7-10) g.

[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0029] 1. The present invention first uses 4,4-dibromomethylbiphenyl, m-tribromomethylbenzene and tetramethylpropylenediamine as monomers, obtains a composite organic substance through reaction, mixes the composite organic substance with a lithium source, a manganese source, an iron source, a phosphate source and polyacrylonitrile to obtain a positive electrode material precursor, and then mixes multi-walled carbon nanotubes, an acid mixed solution, thionyl chloride, sodium azide and aniline to obtain a composite carbon nanotube, which is mixed and pressed with a carbonized positive electrode material to obtain a manganese iron phosphate lithium battery positive electrode material. The material prepared by the method has excellent cycle performance, structural stability and rate performance, and improves the service life of the battery.

[0030] 2. In the present invention, 4,4-dibromomethylbiphenyl and m-tribromomethylbenzene undergo a coupling reaction of aromatic hydrocarbons under the condition of anhydrous ferric chloride as a catalyst to form a prepolymer, and then the prepolymer is dissolved in toluene, tetramethylpropylenediamine is added as a reactant, and a substitution reaction is initiated by heating in an oil bath to obtain a composite organic matter. After mixing it with a spinning solution, the obtained positive electrode material has excellent structural stability, high rate performance and cycle performance. The complex conjugated structure and rigid groups in the composite organic matter can serve as a physical barrier to reduce the volume change of the positive electrode material during the charge and discharge process and improve the structural stability; and the presence of the composite organic matter can improve the electronic conductivity and ion diffusion rate of the positive electrode material, so that it can still maintain good electrochemical properties under high rate charge and discharge conditions; at the same time, the composite organic matter enhances the structural stability and chemical stability of the positive electrode material, reduces the capacity decay and structural damage during the cycle process, and further improves its cycle performance.

[0031] 3. The present invention uses multi-walled carbon nanotubes, acid mixed solution, thionyl chloride, sodium azide and aniline as raw materials to synthesize composite carbon nanotubes, and after ball milling and pressing with carbonized positive electrode materials, obtains a lithium manganese iron phosphate battery positive electrode material with excellent structural stability, high energy density and excellent cycle performance. After the carbon nanotubes are mixed with the carbonized positive electrode material, they can act as a bridge to limit the volume change of the carbonized positive electrode material during the charge and discharge process, prevent it from breaking and pulverizing, thereby improving the overall structural stability of the material; and the composite carbon nanotubes with high conductivity can reduce the internal resistance of the positive electrode material, reduce the loss of energy during the transmission process, and improve the energy output capacity of the material; at the same time, the composite carbon nanotubes can also reduce the generation of interfacial side reactions, keep the surface of the material clean and active, reduce capacity decay and resistance increase, and improve the cycle performance and capacity retention rate of the battery. DETAILED DESCRIPTION

[0032] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] This embodiment discloses a method for preparing a composite organic compound, comprising the following steps:

[0035] Q1: 1.5 g 4,4-dibromomethylbiphenyl and 1.68 g m-tribromomethylbenzene were added to a container, and then 60 mL dichloroethane was added. After ultrasonic treatment for 30 min, 1.43 g anhydrous ferric chloride was added under nitrogen protection. After heating and stirring at 45 ° C for 2 h, the temperature was raised to 85 ° C and the reaction was continued for 2 h. After the reaction was completed, it was diluted with 50vt% methanol solution, filtered, washed, and dried at 85 ° C to obtain a prepolymer;

[0036] Q2: Add 0.27g of the precursor into a container, add 7.5mL of toluene, stir magnetically, then add 1.5mL of tetramethylpropylenediamine, and react in an oil bath at 90°C for 72h. After the reaction is completed, dilute, filter, soak in 50vt% methanol solution for 3 days, filter, wash, and dry at 80°C to obtain a composite organic matter.

[0037] This embodiment discloses a method for preparing composite carbon nanotubes, comprising the following steps:

[0038] S1: 3.0 g of multi-walled carbon nanotubes were added to a container, and a mixed solution of 115 mL of concentrated nitric acid and 37.5 mL of concentrated sulfuric acid was added, and the mixture was heated to 80°C for reflux reaction for 2 h. After the reaction, 62.5 mL of distilled water was added, and the mixture was allowed to stand, and the supernatant was removed, filtered, washed, and dried at 60°C to obtain acidified carbon nanotubes;

[0039] S2: 2.5 g of acidified carbon nanotubes were mixed with 90 mL of thionyl chloride, heated to 75 ° C and refluxed for 12 h under nitrogen protection, and distilled after the reaction to obtain acyl chloride carbon nanotubes. 1.9 g of acyl chloride carbon nanotubes were mixed with 62.5 mL of anhydrous toluene, and 12.5 mg of sodium azide was added, and heated to 65 ° C and refluxed for 6 h under nitrogen protection. After the reflux, 62.5 mL of 50 vt% tetrahydrofuran solution was added, and the temperature was continued to rise to 80 ° C and refluxed for 2 h. After the reflux, the mixture was filtered, washed, and vacuum dried at 82 ° C for 24 h to obtain modified carbon nanotubes.

[0040] S3: 0.57g of modified carbon nanotubes and 225mL of 1mol / L hydrochloric acid were mixed, ultrasonically dispersed for 35min, and then 2.25mL of aniline was added. The mixture was stirred magnetically to obtain a mixed solution. Meanwhile, 5.63g of ammonium persulfate was dissolved in 112.5mL of 1mol / L hydrochloric acid. After mixing evenly, the mixture was added dropwise to 225mL of the mixed solution. The dropping time was controlled to be 4h. After the dropping was completed, the reaction was continued for 12h. After the reaction was completed, the mixture was filtered, washed with acetone for 3 times, and then washed with distilled water until the filtrate was clear. The mixture was dried, ground, and sieved to obtain composite carbon nanotubes.

[0041] This embodiment discloses a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, comprising the following steps:

[0042] Step (1): 0.635 g of lithium carbonate, 1.58 g of manganese tetraoxide, 0.26 g of iron phosphate, 1.29 g of ammonium phosphate and 3 g of polyacrylonitrile with an average molecular weight of 130,000 are added to a container, and then 50 mL of N,N-dimethylformamide is added as a solvent, and the mixture is stirred for 8 h in a water bath at 80°C to obtain a spinning solution. 40 mL of the spinning solution is stirred and mixed with 6.5 g of the composite organic matter, and then subjected to ultrasonic treatment for 20 min, and then electrospinning is performed. During the electrospinning process, the inner diameter of the stainless steel needle is 0.6 mm, the capacity is 10 mL, the voltage during the electrospinning process is 20 kV, the distance between the needle and the collecting device is 12 cm, the spinning solution flow rate is 0.4 mL / h, the humidity is 28%, and the temperature is 26°C, thereby obtaining a positive electrode material precursor;

[0043] Step (2): After aging the cathode material precursor for 12 hours, the precursor is transferred to a tubular furnace for heat treatment. The heat treatment process is as follows: first, pre-oxidation is performed at a pre-oxidation temperature of 230°C, a heating rate of 2°C / min, and a holding time of 2 hours. Then, a carbonization stage heat treatment is performed at a heating rate of 5°C / min, a carbonization time of 4 hours, a carbonization temperature of 750°C, and a carbonization time of 6 hours to obtain a carbonized cathode material.

[0044] Step (3): After ball-milling 2 g of composite carbon nanotubes and 6.5 g of carbonized positive electrode material, the mixture was pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

[0045] Example 2

[0046] This embodiment discloses a method for preparing a composite organic compound, comprising the following steps:

[0047] Q1: 1 g 4,4-dibromomethylbiphenyl and 1.15 g m-tribromomethylbenzene were added to a container, and then 60 mL of dichloroethane was added. After ultrasonic treatment for 30 min, 0.95 g of anhydrous ferric chloride was added under nitrogen protection. After heating and stirring at 45 ° C for 2 h, the temperature was raised to 85 ° C and the reaction was continued for 2 h. After the reaction was completed, it was diluted with 50vt% methanol solution, filtered, washed, and dried at 85 ° C to obtain a prepolymer;

[0048] Q2: Add 0.18g of the precursor into a container, add 5mL of toluene, stir magnetically, then add 1mL of tetramethylpropylenediamine, and react in an oil bath at 90°C for 72h. After the reaction is completed, dilute, filter, soak in 50vt% methanol solution for 3 days, filter, wash, and dry at 80°C to obtain a composite organic matter.

[0049] This embodiment discloses a method for preparing composite carbon nanotubes, comprising the following steps:

[0050] S1: Add 2.4g of multi-walled carbon nanotubes into a container, add a mixed solution of 90mL of concentrated nitric acid and 30mL of concentrated sulfuric acid, heat to 80°C and reflux for 2h, add 50mL of distilled water after the reaction is completed, and let stand.

[0051] The supernatant was removed, filtered, washed, and dried at 60° C. to obtain acidified carbon nanotubes;

[0052] S2: 2g of acidified carbon nanotubes were mixed with 80mL of thionyl chloride, heated to 75°C and refluxed for 12h under nitrogen protection, and distilled after the reaction to obtain acyl chloride carbon nanotubes. 1.5g of acyl chloride carbon nanotubes were mixed with 50mL of anhydrous toluene, and 10mg of sodium azide was added, and heated to 65°C and refluxed for 6h under nitrogen protection. After the reflux, 50mL of 50vt% tetrahydrofuran solution was added, and the temperature was continued to rise to 80°C and refluxed for 2h. After the reflux, the mixture was filtered, washed, and vacuum dried at 82°C for 24h to obtain modified carbon nanotubes.

[0053] S3: 0.38g of modified carbon nanotubes and 150mL of 1mol / L hydrochloric acid were mixed, ultrasonically dispersed for 35min, and then 1.5mL of aniline was added. The mixture was stirred magnetically to obtain a mixed solution. Meanwhile, 3.75g of ammonium persulfate was dissolved in 75mL of 1mol / L hydrochloric acid. After mixing evenly, the mixture was added dropwise to 150mL of the mixed solution. The dropping time was controlled to be 4h. After the dropping was completed, the reaction was continued for 12h. After the reaction was completed, the mixture was filtered, washed with acetone for 3 times, and then washed with distilled water until the filtrate was clear. The mixture was dried, ground, and sieved to obtain composite carbon nanotubes.

[0054] This embodiment discloses a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, comprising the following steps:

[0055] Step (1): 0.55 g of lithium carbonate, 1.375 g of manganese tetraoxide, 0.225 g of iron phosphate, 1.12 g of ammonium phosphate and 3 g of polyacrylonitrile with an average molecular weight of 130,000 are added to a container, and then 50 mL of N,N-dimethylformamide is added as a solvent, and the mixture is stirred for 8 h in a water bath at 80°C to obtain a spinning solution. 30 mL of the spinning solution is stirred and mixed with 5 g of the composite organic matter, and then subjected to ultrasonic treatment for 20 min, and then electrospinning is performed. During the electrospinning process, the inner diameter of the stainless steel needle is 0.6 mm, the capacity is 10 mL, the voltage during the electrospinning process is 20 kV, the distance between the needle and the collecting device is 12 cm, the spinning solution flow rate is 0.4 mL / h, the humidity is 28%, and the temperature is 26°C, thereby obtaining a positive electrode material precursor;

[0056] Step (2): After aging the cathode material precursor for 12 hours, the precursor is transferred to a tubular furnace for heat treatment. The heat treatment process is as follows: first, pre-oxidation is performed at a pre-oxidation temperature of 230°C, a heating rate of 2°C / min, and a holding time of 2 hours. Then, a carbonization stage heat treatment is performed at a heating rate of 5°C / min, a carbonization time of 4 hours, a carbonization temperature of 750°C, and a carbonization time of 6 hours to obtain a carbonized cathode material.

[0057] Step (3): After ball-milling 1 g of composite carbon nanotubes and 7 g of carbonized positive electrode material, the mixture was pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

[0058] Example 3

[0059] This embodiment discloses a method for preparing a composite organic compound, comprising the following steps:

[0060] Q1: 2 g of 4,4-dibromomethylbiphenyl and 2.21 g of m-tribromomethylbenzene were added to a container, and then 60 mL of dichloroethane was added. After ultrasonic treatment for 30 min, 1.91 g of anhydrous ferric chloride was added under nitrogen protection. After heating and stirring at 45 ° C for 2 h, the temperature was raised to 85 ° C and the reaction was continued for 2 h. After the reaction was completed, it was diluted with 50vt% methanol solution, filtered, washed, and dried at 85 ° C to obtain a prepolymer;

[0061] Q2: Add 0.36g of the precursor into a container, add 10mL of toluene, stir magnetically, then add 2mL of tetramethylpropylenediamine, and react in an oil bath at 90°C for 72h. After the reaction is completed, dilute, filter, soak in 50vt% methanol solution for 3 days, filter, wash, and dry at 80°C to obtain a composite organic matter.

[0062] This embodiment discloses a method for preparing composite carbon nanotubes, comprising the following steps:

[0063] S1: 3.6 g of multi-walled carbon nanotubes were added to a container, and a mixed solution of 135 mL of concentrated nitric acid and 45 mL of concentrated sulfuric acid was added, and the mixture was heated to 80°C for reflux reaction for 2 h. After the reaction, 75 mL of distilled water was added, and the mixture was allowed to stand, and the supernatant was removed, filtered, washed, and dried at 60°C to obtain acidified carbon nanotubes;

[0064] S2: 3 g of acidified carbon nanotubes were mixed with 100 mL of thionyl chloride, heated to 75°C and refluxed for 12 h under nitrogen protection, and distilled after the reaction to obtain acyl chloride carbon nanotubes. 2.3 g of acyl chloride carbon nanotubes were mixed with 75 mL of anhydrous toluene, and 15 mg of sodium azide was added. The mixture was heated to 65°C and refluxed for 6 h under nitrogen protection. After the reflux, 75 mL of a 50 vt% tetrahydrofuran solution was added, and the mixture was heated to 80°C and refluxed for 2 h. After the reflux, the mixture was filtered, washed, and vacuum dried at 82°C for 24 h to obtain modified carbon nanotubes.

[0065] S3: 0.76g of modified carbon nanotubes and 300mL of 1mol / L hydrochloric acid were mixed, ultrasonically dispersed for 35min, and then 3mL of aniline was added. The mixture was stirred magnetically to obtain a mixed solution. Meanwhile, 7.5g of ammonium persulfate was dissolved in 150mL of 1mol / L hydrochloric acid. After mixing evenly, the mixture was added dropwise to 300mL of the mixed solution. The dropping time was controlled to be 4h. After the dropping was completed, the reaction was continued for 12h. After the reaction was completed, the mixture was filtered, washed with acetone for 3 times, and then washed with distilled water until the filtrate was clear. The mixture was dried, ground, and sieved to obtain composite carbon nanotubes.

[0066] This embodiment discloses a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, comprising the following steps:

[0067] Step (1): 0.72 g of lithium carbonate, 1.785 g of manganese tetraoxide, 0.295 g of ferric phosphate, 1.455 g of ammonium phosphate and 3 g of polyacrylonitrile with an average molecular weight of 130,000 are added to a container, and then 50 mL of N,N-dimethylformamide is added as a solvent, and the mixture is stirred for 8 h in a water bath at 80°C to obtain a spinning solution. After 50 mL of the spinning solution is stirred and mixed with 8 g of the composite organic matter, the mixture is ultrasonically treated for 20 min, and then electrospinning is performed. During the electrospinning process, the inner diameter of the stainless steel needle is 0.6 mm, the capacity is 10 mL, the voltage during the electrospinning process is 20 kV, the distance between the needle and the collecting device is 12 cm, the spinning solution flow rate is 0.4 mL / h, the humidity is 28%, and the temperature is 26°C, thereby obtaining a positive electrode material precursor;

[0068] Step (2): After aging the cathode material precursor for 12 hours, the precursor is transferred to a tubular furnace for heat treatment. The heat treatment process is as follows: first, pre-oxidation is performed at a pre-oxidation temperature of 230°C, a heating rate of 2°C / min, and a holding time of 2 hours. Then, a carbonization stage heat treatment is performed at a heating rate of 5°C / min, a carbonization time of 4 hours, a carbonization temperature of 750°C, and a carbonization time of 6 hours to obtain a carbonized cathode material.

[0069] Step (3): After ball-milling 3 g of composite carbon nanotubes and 10 g of carbonized positive electrode material, the mixture was pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

[0070] Example 4

[0071] This embodiment discloses a method for preparing a composite organic compound, comprising the following steps:

[0072] Q1: 1.2 g 4,4-dibromomethylbiphenyl and 1.38 g m-tribromomethylbenzene were added to a container, and then 60 mL dichloroethane was added. After ultrasonic treatment for 30 min, 1.27 g anhydrous ferric chloride was added under nitrogen protection. After heating and stirring at 45 ° C for 2 h, the temperature was raised to 85 ° C and the reaction was continued for 2 h. After the reaction was completed, it was diluted with 50vt% methanol solution, filtered, washed, and dried at 85 ° C to obtain a prepolymer;

[0073] Q2: Add 0.21g of the precursor into a container, add 6mL of toluene, stir magnetically, then add 1.2mL of tetramethylpropylenediamine, and react in an oil bath at 90°C for 72h. After the reaction is completed, dilute, filter, soak in 50vt% methanol solution for 3 days, filter, wash, and dry at 80°C to obtain a composite organic matter.

[0074] This embodiment discloses a method for preparing composite carbon nanotubes, comprising the following steps:

[0075] S1: 2.8 g of multi-walled carbon nanotubes were added to a container, and a mixed solution of 107 mL of concentrated nitric acid and 32 mL of concentrated sulfuric acid was added, and the mixture was heated to 80°C for reflux reaction for 2 h. After the reaction, 65 mL of distilled water was added, and the mixture was allowed to stand, and the supernatant was removed, filtered, washed, and dried at 60°C to obtain acidified carbon nanotubes;

[0076] S2: 2.1 g of acidified carbon nanotubes were mixed with 85 mL of thionyl chloride, heated to 75 ° C and refluxed for 12 h under nitrogen protection, and distilled after the reaction to obtain acyl chloride carbon nanotubes. 2.1 g of acyl chloride carbon nanotubes were mixed with 55 mL of anhydrous toluene, and 11 mg of sodium azide was added, and heated to 65 ° C and refluxed for 6 h under nitrogen protection. After the reflux, 58 mL of a 50 vt% tetrahydrofuran solution was added, and the temperature was continued to rise to 80 ° C and refluxed for 2 h. After the reflux, the mixture was filtered, washed, and vacuum dried at 82 ° C for 24 h to obtain modified carbon nanotubes.

[0077] S3: 0.45g of modified carbon nanotubes and 203mL of 1mol / L hydrochloric acid were mixed, ultrasonically dispersed for 35min, and then 1.78mL of aniline was added and magnetically stirred to obtain a mixed solution. At the same time, 4.58g of ammonium persulfate was dissolved in 93mL of 1mol / L hydrochloric acid. After mixing evenly, the mixture was added dropwise to 201mL of the mixed solution. The dropping time was controlled to be 4h. After the addition was completed, the reaction was continued for 12h. After the reaction was completed, the mixture was filtered, washed with acetone three times, and then washed with distilled water until the filtrate was clear, dried, ground, and sieved to obtain composite carbon nanotubes.

[0078] This embodiment discloses a method for preparing a positive electrode material for a lithium manganese iron phosphate battery, comprising the following steps:

[0079] Step (1): 0.595 g of lithium carbonate, 1.43 g of manganese tetraoxide, 0.24 g of iron phosphate, 1.185 g of ammonium phosphate and 3 g of polyacrylonitrile with an average molecular weight of 130,000 are added to a container, and then 50 mL of N,N-dimethylformamide is added as a solvent, and the mixture is stirred for 8 h in a water bath at 80°C to obtain a spinning solution. 45 mL of the spinning solution is stirred and mixed with 5.8 g of the composite organic matter, and then subjected to ultrasonic treatment for 20 min, and then electrospinning is performed. During the electrospinning process, the inner diameter of the stainless steel needle is 0.6 mm, the capacity is 10 mL, the voltage during the electrospinning process is 20 kV, the distance between the needle and the collecting device is 12 cm, the spinning solution flow rate is 0.4 mL / h, the humidity is 28%, and the temperature is 26°C, thereby obtaining a positive electrode material precursor;

[0080] Step (2): After aging the cathode material precursor for 12 hours, the precursor is transferred to a tubular furnace for heat treatment. The heat treatment process is as follows: first, pre-oxidation is performed at a pre-oxidation temperature of 230°C, a heating rate of 2°C / min, and a holding time of 2 hours. Then, a carbonization stage heat treatment is performed at a heating rate of 5°C / min, a carbonization time of 4 hours, a carbonization temperature of 750°C, and a carbonization time of 6 hours to obtain a carbonized cathode material.

[0081] Step (3): 2.5 g of composite carbon nanotubes and 8 g of carbonized positive electrode material are ball-milled and mixed, and then pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

[0082] Comparative Example 1

[0083] Comparative Example 1 Compared with Example 1, in the process of preparing the composite organic matter in Comparative Example 1, 4,4-dibromomethylbiphenyl was not added, and other conditions remained unchanged.

[0084] Comparative Example 2

[0085] Comparative Example 2 Compared with Example 1, in the process of preparing the composite organic matter in Comparative Example 2, no tetramethylpropylenediamine was added, and other conditions remained unchanged.

[0086] Comparative Example 3

[0087] Comparative Example 3 Compared with Example 1, in the process of preparing the composite carbon nanotubes in Comparative Example 3, thionyl chloride was not added, and other conditions remained unchanged.

[0088] Comparative Example 4

[0089] Comparative Example 4 Compared with Example 1, in the process of preparing the composite carbon nanotubes in Comparative Example 4, aniline was not added, and other conditions remained unchanged.

[0090] Comparative Example 5

[0091] Comparative Example 5 Compared with Example 1, in the process of preparing the positive electrode material of the lithium manganese iron phosphate battery in Comparative Example 5, no composite organic matter is added, and other conditions remain unchanged.

[0092] Comparative Example 6

[0093] Comparative Example 6 Compared with Example 1, in the process of preparing the positive electrode material of the lithium manganese iron phosphate battery in Comparative Example 6, no composite carbon nanotubes are added, and other conditions remain unchanged.

[0094] The positive electrode materials of lithium iron manganese phosphate batteries prepared in Examples 1-4 and Comparative Examples 1-6 were punched and cut into discs using a manual slicer, and placed in an 80°C blast drying oven for 10 hours to obtain a positive electrode sheet, with a metal lithium sheet as a counter electrode and a double-layer nickel foam as a gasket. The battery was assembled in the order of positive electrode shell, positive electrode sheet, diaphragm, lithium sheet, double-layer nickel foam gasket, and negative electrode shell, and then packaged by a packaging machine, and the assembled battery was placed in a dryer for 12 hours to obtain a battery. The wet heat cycle stability of the sample was tested according to GB / T 31467.3-2015, the mass energy density of the sample was tested according to GB / T 31467.1-2015, and the cycle performance of the sample was tested according to GB / T31484-2015 according to mass energy density = total energy / total mass. The test results are shown in Table 1:

[0095] Table 1

[0096]

[0097] It can be seen from the test results in Table 1 that the lithium manganese iron phosphate battery positive electrode materials prepared in Examples 1-4 of the present invention have excellent structural stability, excellent cycle performance and rate performance. By comparing Comparative Example 1 with Examples 1-4, it can be seen that the addition of 4,4-dibromomethylbiphenyl can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery; by comparing Comparative Example 2 with Examples 1-4, it can be seen that the addition of tetramethylpropylenediamine can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery; by comparing Comparative Example 3 with Examples 1-4, it can be seen that the addition of thionyl chloride can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery; by comparing Comparative Example 4 with Examples 1-4, it can be seen that the addition of aniline can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery; by comparing Comparative Example 5 with Examples 1-4, it can be seen that the addition of composite organic matter can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery; by comparing Comparative Example 6 with Examples 1-4, it can be seen that the addition of composite carbon nanotubes can effectively improve the structural stability, cycle performance and rate performance of the positive electrode material of lithium iron manganese phosphate battery.

[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0099] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a positive electrode material for a lithium manganese iron phosphate battery, characterized in that: The following steps are involved: Step (1): adding a lithium source, a manganese source, an iron source, a phosphate source and polyacrylonitrile into a container, then adding N,N-dimethylformamide as a solvent, stirring under heating conditions in a water bath to obtain a spinning solution, stirring and mixing the spinning solution with the composite organic matter, ultrasonically treating, and then electrospinning to obtain a positive electrode material precursor; Step (2): after aging the cathode material precursor, transferring it to a tube furnace for heat treatment to obtain a carbonized cathode material; Step (3): After ball-milling the composite carbon nanotubes and the carbonized positive electrode material, the mixture is pressed to obtain a positive electrode material for a lithium manganese iron phosphate battery.

2. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that in the step (1), the lithium source is composed of one or more combinations of lithium carbonate, lithium hydroxide, lithium acetate and lithium chloride; the manganese source is composed of one or more combinations of manganese tetraoxide, manganese dioxide, manganese hydroxide and manganese acetate; the iron source is composed of one or more combinations of ferric phosphate, ferrous oxide, ferrous sulfate and ferrous oxalate; the phosphate source is composed of one or more combinations of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.

3. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that: In the step (1), the molar ratio of the lithium source, the manganese source, the iron source and the phosphate source is (1.5-1.95): (1.2-1.56): (0.3-0.39): (1.5-1.95), the water bath heating temperature is 70-80°C, the stirring time is 6-8h, the amount ratio of the spinning solution to the composite organic matter is (30-50)mL: (5-8)g, the ultrasonic treatment time is 15-20min, and during the electrospinning process, the inner diameter of the stainless steel needle is 0.6mm, the capacity is 10mL, the voltage during the electrospinning process is 20kV, the distance between the needle and the collecting device is 12cm, the spinning solution flow rate is 0.4mL / h, the humidity is 25-30%, and the temperature is 24-28°C.

4. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that: The method for preparing the composite organic matter comprises the following steps: Q1: Add 4,4-dibromomethylbiphenyl and m-tribromomethylbenzene to a container, then add dichloroethane, after ultrasonic treatment, add anhydrous ferric chloride under nitrogen protection, heat and stir, then increase the temperature to continue the reaction, after the reaction is completed, dilute, filter, wash, and dry to obtain the precursor; Q2: Add the precursor to a container, add toluene, stir magnetically, then add tetramethylpropylenediamine, react in an oil bath, and after the reaction is completed, dilute, filter, soak, filter, wash, and dry to obtain a composite organic matter.

5. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 4, characterized in that: In the Q1, the molar ratio of 4,4-dibromomethylbiphenyl, meta-tribromomethylbenzene and anhydrous ferric chloride is (1-2): (1.1-2.1): (2-4), the ultrasonic treatment time is 20-30 min, the heating and stirring temperature is 40-50°C, the stirring time is 1-2 h, the heating temperature is 80-85°C, the continued reaction time is 1-2 h, it is diluted with a 50vt% methanol solution, and the drying temperature is 80-90°C; in the Q2, the amount ratio of the precursor, toluene and tetramethylpropylenediamine is (0.18-0.36) g: (5-10) mL: (1-2) mL, the oil bath reaction temperature is 90-92°C, the reaction time is 70-74 h, it is soaked in a 50vt% methanol solution for 1-3 days, and the drying temperature is 80-82°C.

6. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that: In the step (2), the aging time is 10-12 hours, and the heat treatment process is: first pre-oxidation is performed, the pre-oxidation temperature is 230°C, the heating rate is 2°C / min, and the insulation time is 2 hours, and then a carbonization stage heat treatment is performed, the carbonization stage heating rate is 5°C / min, the carbonization time is 4 hours, the carbonization temperature is 750°C, and the carbonization time is 6 hours.

7. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that: The method for preparing the composite carbon nanotubes comprises the following steps: S1: adding multi-walled carbon nanotubes into a container, adding a mixed solution of concentrated nitric acid and concentrated sulfuric acid, heating and refluxing for reaction, adding distilled water after the reaction is completed, standing, removing the supernatant, filtering, washing, and drying to obtain acidified carbon nanotubes; S2: mixing the acidified carbon nanotubes with thionyl chloride, heating under reflux under nitrogen protection, distilling after the reaction is completed to obtain acyl chloride carbon nanotubes, mixing the acyl chloride carbon nanotubes with anhydrous toluene, adding sodium azide, heating under reflux under nitrogen protection, adding tetrahydrofuran solution after the reflux is completed, continuing to heat and reflux, filtering, washing, and vacuum drying after the reflux is completed to obtain modified carbon nanotubes; S3: The modified carbon nanotubes and hydrochloric acid are mixed, ultrasonically dispersed, and aniline is added. The mixture is stirred magnetically to obtain a mixed solution. Meanwhile, ammonium persulfate is dissolved in the hydrochloric acid. After mixing evenly, the mixture is added dropwise to the mixed solution. The dropping time is controlled. After the dropping is completed, the reaction is continued. After the reaction is completed, the mixture is filtered, washed, dried, ground, and sieved to obtain composite carbon nanotubes.

8. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 7, characterized in that: In S1, the amount ratio of multi-walled carbon nanotubes, concentrated sulfuric acid, concentrated nitric acid and distilled water is (2.4-3.6) g: (90-135) mL: (30-45) mL: (50-75) mL, the heating reflux reaction temperature is 80-85°C, the reaction time is 2-3 h, and the drying temperature is 60-65°C; in S2, the amount ratio of acidified carbon nanotubes and thionyl chloride is (2-3) g: (80-100) mL, the heating reflux temperature is 70-75°C, and the reflux The time is 10-12h, the dosage ratio of acyl chloride carbon nanotubes, anhydrous toluene, sodium azide and tetrahydrofuran solution is (1.5-2.3)g:(50-75)mL:(10-15)mg:(50-75)mL, the heating reflux temperature is 60-70℃, the time is 6-8h, the volume fraction of tetrahydrofuran solution is 50vt%, the heating reflux temperature is 80-85℃, the time is 1-2h, the vacuum drying temperature is 80-85℃, and the time is 20-24h.

9. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 7, characterized in that: In the S3, the dosage ratio of modified carbon nanotubes, hydrochloric acid and aniline is (0.38-0.76) g: (150-300) mL: (1.5-3) mL, the ultrasonic dispersion time is 30-45 min, the dosage ratio of ammonium persulfate, hydrochloric acid and mixed solution is (3.75-7.5) g: (75-150) mL: (150-300) mL, the dropwise addition time is 4-6 h, the continued reaction time is 10-12 h, and the product is first washed with acetone for 3-5 times, and then washed with distilled water until the filtrate is clear.

10. The method for preparing a positive electrode material for a lithium manganese iron phosphate battery according to claim 1, characterized in that: In the step (3), the usage ratio of the composite carbon nanotubes and the carbonized positive electrode material is (1-3) g: (7-10) g.

Citation Information

Cited By

  • Preparation method of multi-walled carbon nanotube conductive agent for lithium ion battery

    CN122233366A